Tindak Tutur Ilokusi pada Interaksi Jual Beli di Pasar Inpres Ruteng dalam Bahasa Manggarai: Kajian Pragmatik - Stanislaus Hermaditoyo; Yohanes Wendelinus Dasor; Gregorius Raru; Flora Ana Yanti (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2023)
The purpose of this study was to describe illocutionary speech acts in the interaction of selling and buying in the Ruteng Inpres market in Manggarai, pragmatic studies. This type of research is descriptive qualitative. The data obtained were described using words. Sources of data in this study are sellers and buyers of vegetables, fish, bags, and clothes. At the same time, the data is the spoken language spoken by sellers and buyers who are conducting buying and selling transactions at the Inpres market in Ruteng in Manggarai. Data collection using the observation method with record and note techniques. This study's findings indicate that the bargaining interactions in the Ruteng Presidential Market are illocutionary (representative / assertive, directive, expressive, commissive, and declaration). The most dominant speech acts are directive acts (begging, ordering, questioning). In conversation, there is also a structure that is bounded by a pair of adjoining / side by side. There were eight patterns of adjacent / compatible couples found in the bargaining interactions at the Ruteng Presidential Market, including (1) greeting-greeting patterns, (2) call-answer patterns, (3) information-giving request patterns, (4) the complaint-admit pattern, (5) the requestallowance pattern, (6) the offer-acceptance pattern, (7) the offer-rejection pattern (8) the question-answer pattern.